The conscience code lead with your values. advance your career. - Shell, G. Richard (Nashville HarperCollins Leadership, 2021)
The Conscience Code: Solves a crucial problem faced by professionals everywhere: What should they do when they are asked to compromise their core values to achieve organizational goals? Teaches readers to recognize and overcome the five organizational forces that push people toward actions they later regret. Lays out a systematic, values-to-action process that people at all levels can follow to maintain their integrity while achieving true success in their lives and careers. Driven by dramatic, real-world examples from Shell's classroom, today's headlines, and classic cases of corporate wrongdoing, The Conscience Code shows how to create value-based workplaces where everyone can thrive
Keywords: BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Workplace Culture